2014
DOI: 10.1086/678597
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Practice: Factors That Influence Physician Hand Hygiene Compliance

Abstract: We identified several key determinants that physicians believe influence whether and when they practice hand hygiene at work. These beliefs identify potential individual, team, and organization targets for behavior change interventions to improve physician hand hygiene compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 36 publications
6
58
0
4
Order By: Relevance
“…With respect to the factors that hindered HH, it should be noted that they were consistent with those reported in the literature, which were generally related to professional category, physical and structural factors, material resources, knowledge, beliefs, goals, memory, attention, and decision making (6,8,(17)(18) . The type of HH procedure (simple cleaning or ABH) used most frequently by professionals varies according to country, study type, and intervention (19)(20)(21) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…With respect to the factors that hindered HH, it should be noted that they were consistent with those reported in the literature, which were generally related to professional category, physical and structural factors, material resources, knowledge, beliefs, goals, memory, attention, and decision making (6,8,(17)(18) . The type of HH procedure (simple cleaning or ABH) used most frequently by professionals varies according to country, study type, and intervention (19)(20)(21) .…”
Section: Discussionsupporting
confidence: 83%
“…However, in other studies, including Canadian Overall, respondents indicated a statistically significant preference for soap and water over ABH (4) . The reasons for this choice vary and include the feeling that hands are clean after using soap and water in HH, low tolerance of the alcohol-based product offered by the institution, lack of knowledge/training, behavioral and cultural factors, and institutional safety culture (1,4,(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…Los cirujanos declararon que no eran influidos por otros miembros del equipo en su práctica de la higiene de manos, tal vez debido a que los cirujanos deben trabajar más independientemente que los médicos que tienden a trabajar más en equipo. 9 Las limitaciones del sistema en cuanto a recursos son una barrera importante para que el médico realice higiene de manos, principalmente a facilitar el acceso en el sitio de atención del paciente. Las altas cargas de trabajo también se surgieren como una limitación.…”
Section: Discussionunclassified
“…3 Additionally, provider experience may be linked to a more casual attitude toward infection prevention precautions. 4 Virginia Hospital Center (VHC) is a 334-bed teaching hospital in Arlington, Virginia, located in the Washington, D.C., metropolitan area. Hand hygiene rates have historically beeñ 50%-60% among providers, and they have increased since 2012 to 85% with stronger emphasis on hand hygiene.…”
Section: Specialty But Not Age Is Related To Provider Hand Hygiene mentioning
confidence: 99%